The Quarrel and its Verses and Hadiths - an Objective Study- - Zahra , Salah (Islamic Sciences Journal, 2023)
ABSTRACT This research aims to clarify the deep dimension of antagonism and the paths of reform are many and varied. This research included a preliminary, three topics and a conclusion: I mentioned in the first topic / the definition of litigation and the places in which the word “rivalry” was mentioned in the Holy Qur’an and its meanings. In the second topic / I mentioned the rivalry in the prophetic Sunnah and its impact on the individual and society